Sulfated Cholecystokinin-8 Promotes CD36—Mediated Fatty Acid Uptake into Primary Mouse Duodenal Enterocytes - Demenis, Claire; McLaughlin, John; Smith, Craig P. (Frontiers in Physiology, 2017)
Cholecystokinin (CCK) is an archetypal incretin hormone secreted by intestinal enteroendocrine cells (EEC) in response to ingested nutrients. The aim of this study was to determine whether CCK modulates enterocyte fatty acid uptake by primary mouse duodenal cells. Exposure of primary mouse duodenal cells to 10 pM sulphated CCK-8 caused a two fold increase in dodecanoic acid fatty acid (FA) uptake. The selective CCK A receptor antagonist loxiglumide (100 μM) completely abolished the CCK-8 induced FA uptake. The CD36 fatty acid translocase-specific inhibitor sulfo-N-succinimidyl oleate (1 µM) also completely inhibited CCK-8 induced FA uptake, as did treatment with 200 µM phloretin. Together these data show CCK induces FA uptake into duodenal enterocytes; this action involves the CCK-RA receptor and is carrier mediated by CD36.